The Mathematics Teachers’ Specialized Knowledge (MTSK) model in the Web of Science until 2020 - Moriel Junior, Jeferson Gomes (Universidade Estadual de Campinas, 2021)
The aim of this work is to map the production related to the Mathematics Teachers’ Specialized Knowledge Model in the Web of Science database. For this, we carried out an analytical-descriptive research, with an exploratory-bibliometric approach. We found a corpus of 37 papers from 2013 to 2020 and analyzed: Indexing on the Web of Science; Distribution by year and types of documents; Authors; Development institutions and agencies; Countries and languages; brief Analysis of citations and Keywords. The results allow us to conclude that MTSK production is collaborative and global, involving at least 9 countries in Europe and Latin America, in a network movement that contributes to global dissemination and, in a way, is configured as an international validation test in different school cultures and contexts of teaching practice and training.